Field data for larches growing in the Taimyr treeline ecotone. - Kruse, Stefan; Gerdes, Alexander; Kath, Nadja J; Epp, Laura Saskia; Stoof-Leichsenring, Kathleen Rosmarie; Pestryakova, Ludmila A; Herzschuh, Ulrike (PANGAEA, 2019)
The table contains the biallelic data for 8 loci (LOCUS#: "K241", "Ld56", "K225", "K224", "Ld45", "K235", "K260", "K066") for 612 Larix gmelinii individuals sampled within 100x100 m from site TY04-V1 located on the Taymyr Peninsula, Russia. This site is part of a dataset see further details in https://doi.pangaea.de/10.1594/PANGAEA.874612.
Microsatellite marker data for 8 nuclear microsatellite loci from Dahurian larch (Larix gmelinii) individuals sampled at site TY04VI on the Taymyr Peninsula, north-central Siberia
Keywords: Allele fragment length; AWI_Envi; Class; Dispersal; FTe; Parentage; Polar Terrestrial Environmental Systems @ AWI; Sample code/label; Siberia; SSR; Treeline; TY04VI